Behavior Change Communication (BCC) Campaign Management through New Media for Field Officer of Igama and Wamarapa HIV/AIDS Prevention Program in Malang - Nirwana, Maya Diah; Riani, Yuyun Agus; Handayani, Sri (International Journal of Social and Local Economic Governance, 2016)
Methods and communication strategy are needed in order to form the safe attitude and behavior of the HIV/AIDS (Human Immunodeficiency Virus-Acquired Immunodeficiency Syndrome) prevention target group, of which the character, situation, and condition of the target group have become an important attention and consideration for Field Officer for the effectiveness of activity. BCC is a communication tools on behavior change that is developed on HIV/AIDS prevention program. The FGD of the consultant team with field officer shows that almost all the Field Officers of the institutions in implementing HIV/AIDS prevention programs, have not been fully able to produce and utilize BCC campaign media due to skill constraints. This paper provides an understanding on how to produce the right online media, as well as to utilize communication technology which is affordable and easy in supporting Field Officer’s role and function on the prevention of HIV/AIDS. In addition to producing BCC campaign media, this activity also carries out facilitation in the form of counseling and monitoring the activity’s result process. Ikatan Gay Malang (IGAMA) dan Waria Malang Raya Peduli AIDS (WAMARAPA) have become partners in this community development activity. After training and mentoring, the Field Officers are expected to be able to utilize new media, especially Facebook, WA (WhatsApp), and BBM (BlackBerry Messenger) to conduct BCC campaign of HIV/AIDS prevention based on netiquette.Keywords: Campaign, BCC, New Media, HIV/AIDS